THE ROLE OF SCIENTIFIC KNOWLEDGE IN WISŁAWA SZYMBORSKA’S POETIC CREATION OF THE LIFEWORLD. PART I - Józef Leszek Krakowiak (Filozofia i Nauka, 2022)
This paper is the first part of the research on Wisława Szymborska’s reflections and considerations — in poetic form — on knowledge, science, and the scientific worldview. These aspects of Szymborska’s work are presented on the wide background of the philosophical threads in her poetry.